2011
DOI: 10.1111/j.1440-1789.2011.01286.x
|View full text |Cite
|
Sign up to set email alerts
|

An MND/ALS phenotype associated with C9orf72 repeat expansion: Abundant p62‐positive, TDP‐43‐negative inclusions in cerebral cortex, hippocampus and cerebellum but without associated cognitive decline

Abstract: The transactive response DNA binding protein (TDP-43) proteinopathies describe a clinico-pathological spectrum of multi-system neurodegeneration that spans motor neuron disease/amyotrophic lateral sclerosis (MND/ALS) and frontotemporal lobar degeneration (FTLD). We have identified four male patients who presented with the clinical features of a pure MND/ALS phenotype (without dementia) but who had distinctive cortical and cerebellar pathology that was different from other TDP-43 proteinopathies. All patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 39 publications
9
93
1
Order By: Relevance
“…4). This evidence supports that the abnormal accumulation of TDP-43, p62, and ubiquitin seen in patients with ALS and FTD with C9orf72 expansions (21,(38)(39)(40) is not induced by a loss of C9orf72 function mRNA and supports that ASO-mediated C9orf72 reductions should be tolerated in an adult nervous system and may be safe to use in ALS and FTD.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…4). This evidence supports that the abnormal accumulation of TDP-43, p62, and ubiquitin seen in patients with ALS and FTD with C9orf72 expansions (21,(38)(39)(40) is not induced by a loss of C9orf72 function mRNA and supports that ASO-mediated C9orf72 reductions should be tolerated in an adult nervous system and may be safe to use in ALS and FTD.…”
Section: Discussionsupporting
confidence: 75%
“…Abnormal aggregations of TDP-43, p62, and ubiquitin have been extensively described in the neuropathology of ALS and FTD with C9orf72 expansion (21,(38)(39)(40). After 18 wk of ASOmediated depletion of C9orf72 RNA, examination of tissue sections revealed that TDP-43 remained mainly nuclear in spinal cord, hippocampus, and cortex (Fig.…”
Section: Ggggccmentioning
confidence: 77%
See 1 more Smart Citation
“…30 Consistent with our results, a recent study found mild to moderate p62 and TDP-43 staining in the thalamus of 4 C9ϩ carriers with MND. 31 Thalamic atrophy has been described in FTLD-TDP type A, 5,32 but not in type B, which is typically associated with FTD-MND. Although most FTD-MND cases show FTLD-TDP type B histology, an unexpected feature of C9ORF72 pathology is the frequency of FTLD-TDP type A.…”
Section: Demographicsmentioning
confidence: 99%
“…30 TDP-43 inclusions are also prominent in cases linked to chromosome 9p 31 but HREM-specific pathology includes abundant cytoplasmic and intranuclear p62-positive inclusions in the hippocampus and cerebellum that are TDP-43-negative. 32,33 Precisely, how the HREM causes TDP-43 mislocalisation and neurodegeneration is not currently known. Evidence that the HREM reduces levels of C9ORF72 transcripts implicates a loss of function, however, probes detecting the HREM transcript identified RNA foci within the nuclei of neurons in the frontal cortex and spinal cord.…”
Section: Human_reference : Gcgcgctaggggccggggccggggcc---------------mentioning
confidence: 99%